The Course of Acute Intestinal Infections in Children Associated with Candidiasis Infection - Rashidov, F. A.; Rikhsiyeva, G. M.; Mirismoilov, M. M.; Umarov, T. U. (American Journal of Bioscience and Clinical Integrity, 2024)
This study examines the clinical progression of acute intestinal infections (AII) in children aged 6 months to 3 years, who were hospitalized for diarrhea of unclear origin linked to candidiasis infection. The indiscriminate use of broad-spectrum antibiotics is recognized as a factor contributing to the proliferation of Candida spp. The correlation between Candida spp. and severe diarrhea leads to persistent intoxication, intestinal impairment, and an extended recovery duration.